1999
DOI: 10.1017/s0029665199000397
|View full text |Cite
|
Sign up to set email alerts
|

The influence of maternal nutrient restriction in early to mid-pregnancy on placental and fetal development in sheep

Abstract: Placental weight is a primary factor determining size at birth in many species. In sheep, placental weight peaks at approximately mid-gestation, with structural remodelling occurring over the second half of pregnancy to meet the increasing nutritional demands of the growing fetus. Numerous factors influence placental growth and development in sheep, and many workers (see Kelly, 1992) have investigated the role of maternal nutrition as a regulator of placental and fetal size. We have studied the effects of feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 29 publications
7
46
1
Order By: Relevance
“…Various NR protocols in other animal species have yielded variable outcomes for fetal organ and total body weights. In sheep, mild and moderate maternal NR (30-50%) during early gestation (the period of maximal placental growth and the time comparable to the maternal NR period in our study) induced no decrease in fetal body weight, consistent with our findings [26]. As in our study, Osgerby et al [27] detected no differences in placental weight when ewes were exposed to 30% maternal NR during the first half of gestation.…”
Section: Maternal and Fetal Growth-maternalsupporting
confidence: 92%
“…Various NR protocols in other animal species have yielded variable outcomes for fetal organ and total body weights. In sheep, mild and moderate maternal NR (30-50%) during early gestation (the period of maximal placental growth and the time comparable to the maternal NR period in our study) induced no decrease in fetal body weight, consistent with our findings [26]. As in our study, Osgerby et al [27] detected no differences in placental weight when ewes were exposed to 30% maternal NR during the first half of gestation.…”
Section: Maternal and Fetal Growth-maternalsupporting
confidence: 92%
“…This may be a reflection of the nutrient constraint caused by lactation during the majority of the gestation in these dams, despite the attempts for compensation during the dry period. Heasman et al (1999) found similar results in nutrient restricted sheep. The nutritional challenge was followed by an enhancement of the fetal component of the placenta when nutritional level was restored, leading to a disproportionally larger placental to fetal weight ratio and thus a reduced placental efficiency.…”
Section: Discussionsupporting
confidence: 68%
“…Placental weight is the major factor determining lamb birth weight (Mellor, 1983;Heasman et al, 1999). Peak placental weight is attained by day 80 of gestation (Heasman et al, 1999) and is sensitive to nutrition between days 40 and 80 of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Peak placental weight is attained by day 80 of gestation (Heasman et al, 1999) and is sensitive to nutrition between days 40 and 80 of gestation. In the current study the high and low herbage allowances resulted in moderate and mild undernutrition, respectively.…”
Section: Discussionmentioning
confidence: 99%